A comparative study of quality properties of pelletized agricultural and forestry lopping residues - Zamorano, M; Popov, V; Rodriguez, M L; Garcia-Maraver, A (RENEWABLE ENERGY, 2011)
Biomass is an abundant renewable energy source; however, because of its characteristics it is not easily used in its original form. Pelletization technology represents mass and energy densification that provides easier biomass fuel handling and feeding. A privately owned pelletization industrial plant has been set up to produce pellets from agricultural and forestry lopping residues. The plant has produced so far pellets made of leaves of olive tree, a mixture of different parts of olive trees, almond trees, black poplar and holm oak trees. The characteristics of the resulting products have been analyzed in this research to foresee their behaviour in the combustion process. Parameters analyzed included particle and bulk density, moisture content, crushing resistance or hardness, number of particles of pellets per unit volume, size (including diameter, length and ratio of both values), percentage of carbon, nitrogen, sulphur and hydrogen, additives and ash content, and finally heating value. Relationships between various parameters and a comparison with guidelines established by some European norms have been also investigated in order to determine possible restrictions on the use of the pellets. Results have shown that the use of different types of raw materials from agricultural and forestry lopping residues results in different physical and chemical properties of the pellets defining their possible application. Relationships between several parameters of pellets and a comparison with some European norms guidelines were also investigated and different guidelines fulfilment were detected; however no pellets tested fulfilled all parameters from guidelines established in the norms considered. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Agricultural waste; Lopping residues; Norms; Pellets; Properties; Quality properties

Cork and Alcoholic Beverages - Maga, Joseph A; Puech, Jean-Louis (Food Reviews International, 2005)
For centuries, cork has been the stopper of choice for various alcoholic beverages. In this review, cork history, sources, production, physical properties, composition, off-flavors, and alternatives to cork stoppers are discussed.
doi: 10.1081/FRI-200040593
Keywords: Alternatives; composition; production; Properties; stoppers; Taint

Cork and Alcoholic Beverages - Maga, Joseph A.; Puech, Jean-Louis (Food Reviews International, 2005)
For centuries, cork has been the stopper of choice for various alcoholic beverages. In this review, cork history, sources, production, physical properties, composition, off-flavors, and alternatives to cork stoppers are discussed.
doi: 10.1081/FRI-200040593doi: 10.1081/FRI-200040593The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Alternatives; composition; production; Properties; stoppers; Taint